Acorn predation and seedling production in a low-density population of cork oak (Quercus suber L.) (Forest Ecology and Management, 1995)
Prospects for cork oak recruitment were examined in a scrub-dominated area with low tree density in southern Spain by sowing acorns experimentally in a variety of sites. Seeds placed on the ground surface were invariably eaten within a few months by a variety of vertebrate herbivores (cattle, red deer, fallow deer, wild boar and rabbits). Predation reached 100% whether acorns were placed beneath trees or more than 100 m away from trees. Seeds placed under dense heath scrub were also rapidly removed, although their final fates could not be ascertained. Single acorns buried under open or dense scrub experienced the lowest predation (52% and 0%, respectively) and had relatively high emergence rates (38% and 60%, respectively). Heavy shoot browsing occurred in both scrub types, and out of the 49 buried acorns which produced a shoot, only two seedlings were alive 1 year after germination. None survived 2 years after sowing.